梅毒与民国性病文化建构： 以上海报刊和小说为中心 = Syphilis and the cultural construction of venereal diseases in the Republic of China: focusing on the Shanghai Press and fictions - 孟嘉杰 Meng, Jiajie (Nanyang Technological University, 2022)
上海 1843年开埠后，性病迅速在城市蔓延其中梅毒的传播态势最为严峻。 年开埠后，性病迅速在城市蔓延其中梅毒的传播态势最为严峻。 年开埠后，性病迅速在城市蔓延其中梅毒的传播态势最为严峻。 疾病泛滥不只带来生理上的疼痛，污名 疾病泛滥不只带来生理上的疼痛，污名 、知识 、知识 与商机亦随之而来。然，既往研 与商机亦随之而来。然，既往研 与商机亦随之而来。然，既往研 究未注意到这一疾病与当时的 科学 、政治 、政治 、经济与 、经济与 文化的密切关系。因此，本研 文化的密切关系。因此，本研 文化的密切关系。因此，本研 究从医疗人文视角出发，以民国时期的《申报》与张资平小说创作为对象考 究从医疗人文视角出发，以民国时期的《申报》与张资平小说创作为对象考 究从医疗人文视角出发，以民国时期的《申报》与张资平小说创作为对象考 究从医疗人文视角出发，以民国时期的《申报》与张资平小说创作为对象考 究从医疗人文视角出发，以民国时期的《申报》与张资平小说创作为对象考 察这一时期的性病文化建构如何与当知识嬗变、转型政治现实相互动。 察这一时期的性病文化建构如何与当知识嬗变、转型政治现实相互动。 《申报》的梅毒社论、新闻道与医药凸显了这一时期旧并陈样貌：针 《申报》的梅毒社论、新闻道与医药凸显了这一时期旧并陈样貌：针 《申报》的梅毒社论、新闻道与医药凸显了这一时期旧并陈样貌：针 《申报》的梅毒社论、新闻道与医药凸显了这一时期旧并陈样貌：针 砭梅毒的社论凸显了上海半殖民近况，而有关新闻则以强烈道德立场训诫疾 砭梅毒的社论凸显了上海半殖民近况，而有关新闻则以强烈道德立场训诫疾 病的传播者，不 仅受害人隐私被完全牺牲报道所涉及同性行为更是病的传播者，不 仅受害人隐私被完全牺牲报道所涉及同性行为更是病的传播者，不 仅受害人隐私被完全牺牲报道所涉及同性行为更是断放大、异化。医药 断放大、异化。医药 断放大、异化。医药 广告则同时挪用东、西病理论述，在突出自身权威性与有效 广告则同时挪用东、西病理论述，在突出自身权威性与有效 广告则同时挪用东、西病理论述，在突出自身权威性与有效 性之余，兼顾普通读者的理解力；广告插画对患视觉再现则持续压抑女 性之余，兼顾普通读者的理解力；广告插画对患视觉再现则持续压抑女 性之余，兼顾普通读者的理解力；广告插画对患视觉再现则持续压抑女 性之余，兼顾普通读者的理解力；广告插画对患视觉再现则持续压抑女 性的 疾病经验，并确立新的医学权威。张资平小说出现了大量梅毒患者其 疾病经验，并确立新的医学权威。张资平小说出现了大量梅毒患者其 疾病经验，并确立新的医学权威。张资平小说出现了大量梅毒患者其 疾病经验，并确立新的医学权威。张资平小说出现了大量梅毒患者其 描写疾 病经验时刻意突出自身的科学性，而女最后皆成为对其份否定。 病经验时刻意突出自身的科学性，而女最后皆成为对其份否定。 从材料收集的角度，本 从材料收集的角度，本 研究梳理、分析了大量长期为学界忽略的《申报》性 研究梳理、分析了大量长期为学界忽略的《申报》性 研究梳理、分析了大量长期为学界忽略的《申报》性 研究梳理、分析了大量长期为学界忽略的《申报》性 病社论、报道与医药广告， 病社论、报道与医药广告， 且同时涵盖了文字材料与图像，并进而集中呈现 同时涵盖了文字材料与图像，并进而集中呈现 了民国知识分子对梅毒的看法以及相关病理论述。在史料搜集基础上，本文结 了民国知识分子对梅毒的看法以及相关病理论述。在史料搜集基础上，本文结 了民国知识分子对梅毒的看法以及相关病理论述。在史料搜集基础上，本文结 了民国知识分子对梅毒的看法以及相关病理论述。在史料搜集基础上，本文结 合医学人文、后殖民研究性别的众多理论方法， 合医学人文、后殖民研究性别的众多理论方法， 合医学人文、后殖民研究性别的众多理论方法， 合医学人文、后殖民研究性别的众多理论方法， 从而 回应 、反思、 批判 现 行中国研究领域的现代性、杂糅公共空间文化翻译以及身份建构等问题。 行中国研究领域的现代性、杂糅公共空间文化翻译以及身份建构等问题。 行中国研究领域的现代性、杂糅公共空间文化翻译以及身份建构等问题。 Since Shanghai opened its port in 1843, venereal diseases have spread rapidly in the city, with syphilis being the most severe form of transmission. In addition to causing physical suffering, the spread of venereal diseases also increased stigma, knowledge, and business prospects. The intimate connection between venereal diseases and the scientific, political, economic, and cultural factors of the time, however, has not been addressed in earlier studies. This study adopts a medical humanities perspective to investigate how the cultural construction of venereal disease in Republican Shanghai interacted with the intellectual transitions, cultural transformations, and political realities by taking Shun Pao as well as Zhang Ziping’s fiction as objects. Reportage, editorials, and advertisements in Shun Pao highlight the coexistence of the old and the new: editorials on syphilis emphasize the semi-coloniality of Shanghai, and news reports condemn the spreaders with a strong moral stance, completely sacrificing the privacy of victims while also exaggerating and alienating the homosexuality. Western and Eastern pathological discourses in medical ads are appropriated to ensure that average readers can understand them and to reinforce their legitimacy and authority. In advertisements, the visual representation of patients continued to repress women’s experiences with the disease and construct a new medical authority. Zhang Ziping’s novels feature a large number of syphilis patients, and his narration of the disease experience is always intended to showcase his own scientific nature; in contrast, women’s experience of venereal diseases eventually becomes a denial of their identity. This study first gathers multiple textual and visual materials from Shun Pao to compensate for the lack of previous attention paid to the spread of venereal disease in Republican Shanghai. On top of that, this project also incorporates a variety of theoretical methods, such as medical humanities, postcolonial studies, and gender studies, to respond to and reflect on the issues of modernity, hybridity, public sphere, cultural translation, and identification in the current field of Chinese studies.